Synthesis, Characterization and Biological Evaluation of New Dithiocarbamate Ligand and Its Complexes with some Metal Ions - Numan, Ahmed T.; Ibraheem, Kaiss R.; Ibrahim, Mohammed K. (Ibn AL-Haitham Journal For Pure and Applied Sciences, 2017)
New bidentate dithiocarbamate ligand (NaL) namely [Sodium-2-(((3-methyl -4- â€œ(2,2,2-tri fluoro ethoxy) pyridin-2â€-yl) methyl) sulfinyl)-1H-benzoimidazole -1-carbodithioate] was prepared. This free ligand was synthesized from the reaction of a (RS)-2-([3-methyl -4-(2,2,2-tri fluoroethoxy) pyridin-2-yl] methyl sulfinyl)-1H benzoimidazole, CS2 and NaOH in methanol as solvent. From reaction of dithiocarbamate salt (NaL) with metal ions (M); Co(II), Ni(II), Cu(II), Zn(II), Cd(II) and Pd(II)â€, have obtained  the DTC complexes at general molecular formula [M(L)2(H2O)2] and [Pd(L)2]. To characterize the ligand and its complexes, used different analyses methods such FTIR, UV-Vis, elemental microanalysis, atomic absoreption, magnetic susceptibility, conductance, melting points, 1H- 13C- NMR spectroscopy, thermal analysis and mass spectrum.  These studies indicated the formation of DTC complexes which their geometries about metal centers are octahedral; except Pd-complex is square planer. The bacterial activity evaluation against investigated bacterial species indicated that the metal complexes are more active than the free ligand when compared them.